2021
DOI: 10.11646/zootaxa.4941.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Two New Species of Diploderma Hallowell, 1861 (Reptilia: Squamata: Agamidae) from the Hengduan Mountain Region in China and Rediscovery of D. brevicaudum (Manthey, Wolfgang, Hou, Wang, 2012)

Abstract: Recent studies have highlighted the underestimated diversity of the genus Diploderma Hallowell, 1861 in the Hengduan Mountain Region in Southwest China, but much of the region remains poorly surveyed for reptile diversity. In this study we describe two new species of Diploderma from the upper Jinsha and middle Yalong River Valley, based on evaluations of morphological, genetic, and distribution data. The two new species are morphologically most similar to D. angustelinea and D. vela, but they can be diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Allopatric distribution across the Hengduan Mountain Region have been suggested to create reproductive isolation through geographic isolation ( Wang et al 2015 , 2021a ; Dong et al 2020 ). Wang et al (2021b) considered that D. drukdaypo may represent a recently diverged species from the D. vela lineage, adapted to higher-elevated habitats in the upper Mekong River valley, and suggested that further studies are needed to gain a better understanding of gene flow and speciation mechanisms between these two sister species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Allopatric distribution across the Hengduan Mountain Region have been suggested to create reproductive isolation through geographic isolation ( Wang et al 2015 , 2021a ; Dong et al 2020 ). Wang et al (2021b) considered that D. drukdaypo may represent a recently diverged species from the D. vela lineage, adapted to higher-elevated habitats in the upper Mekong River valley, and suggested that further studies are needed to gain a better understanding of gene flow and speciation mechanisms between these two sister species.…”
Section: Discussionmentioning
confidence: 99%
“…We compared morphological characters of the new species with other members of the genus relying on examined specimens and original species descriptions ( Hallowell 1861 ; Günther 1864 ; Anderson 1878 ; Boulenger 1906 , 1918 ; Barbour and Dunn 1919 ; Stejneger 1924 ; Mertens 1926 ; Smith 1935 ; Gressitt 1936 ; Bourret 1937 ; Song 1987 ; Ota 1989 ; Ota et al 1998 ; Li et al 2001 ; Gao and Hou 2002 ; Manthey et al 2012 ; Wang et al 2015 , 2016 , 2019b , d , 2021a , b , 2022a ; Ananjeva et al 2017 ; Rao et al 2017 ; Liu et al 2020 , 2022 ; Cai et al 2022 ), and the additional data from Wu et al (2005) , Manthey (2008) , and Wang et al (2017 , 2018 , 2019b , c , 2021a , 2022b ).…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the species inhabiting forests are relatively less threatened by humans. On the contrary, if a section of a river valley is destroyed, such as by expansion of townships and agricultural lands, construction of tourist sites, development of highways and construction of hydroelectric plants (Wang et al 2016(Wang et al , 2019b(Wang et al , 2021a, the endemic species there may become extinct. Therefore, the species inhabiting river valleys are more vulnerable to human threats.…”
Section: Discussionmentioning
confidence: 99%
“…Diploderma Hallowell, 1861, is a genus including 36 species recognised currently (Uetz et al 2022;Wang et al 2022). Of the total diversity, 34 species are distributed in China, of which 22 species are only distributed in the Hengduan Mountain Region of south-western China (Wang et al 2021a(Wang et al , 2022.…”
Section: Introductionmentioning
confidence: 99%